Biografemática e formação: fragmentos de escrita de uma vida - GONÇALVES, Jadson Fernando Garcia (Universidade Federal do Pará, 2013)
The present work has as research object the auto-biographems in the context of teachers formation. It analyses a set of texts of autobiographical characteristics extracted from the proceedings of the International Meting on (Auto)biographical Research – CIPA – of 2006, 2008 and 2010. The study is focused, mainly, on the notion of biographem, and on the problematization of Writing of Life in autobiographical texts of teachers of higher education – as presented on the mentioned editions of CIPA. Setting Writing of life (on its autobiographical form) as a problem, shows the changing alternatives (characterized by encounters, dis-encounters, bifurcations, links, contiguities, sinuosities, fragmentations) of a life. A written life, not as a direct and veridical correspondence with life, but as a possibility of creation, of invention of a writing of life that produce some kind of influence... Details of a life, strokes, spaces, holes, fragments that cast a spell, touch, scape from the text and get into our lives; details that produce a co-existence: joy of writing: immanent artifice of a life. This work, as an exercise of critic, does not propose an analysis of auto-biographical texts from a judicative our veridical perspective, it does not aim to criticize the object or the form of writing, but it aims to offer a collection of fragments, lines, sentences of pleasure that allow to link life and writing, a life crossing through lines of writing, a life as fault, crack of lines of writing. It also imply an affirmation, as force-idea of this thesis-experiment, of the impossibility of “imprisoning” life into an Auto-biography-destiny and proposal of a auto-biography-drift.